Kompetensi Mengadili Peradilan Tata Usaha Negara Terhadap Gugatan Perbuatan Melanggar Hukum Oleh Badan Dan/Atau Pejabat Pemerintahan (Onrechtmatige Overheidsdaad) - Muhammad Alifian Geraldi Fauzi; Anna Erliyana (UNES Law Review, 2023)
The competence to adjudicate the PTUN was previously very narrow, only having the authority to adjudicate state administrative decisions (beschikking) in the concrete, individual, and final sense as regulated in the PTUN Law. However, since the enactment of the UUAP, there has been a reverse flow of legislative policy which has led to the expansion and confirmation of the PTUN's authority in adjudicating government administration disputes. Implementation of the expansion of authority regarding the authority to adjudicate claims against unlawful acts by government bodies and/or officials. The broad implication of the competency to adjudicate state administration trade after the enactment of the UUAP is the transfer of competence to adjudicate against unlawful acts by government bodies and/or officials (onrechtmatige overheidsdaad/OOD) from the District Court to competence to adjudicate the State Administrative Court and the tangential point regarding the authority to adjudicate between the two courts, namely the District Court and the State Administrative Court, the Supreme Court as the highest holder of judicial authority has regulated this by issuing a PERMA which is Lex Specialist to regulate this matter. Based on Supreme Court Regulation (PERMA) Number 2 of 2019 concerning Settlement Guidelines regulating Government Actions and the Authority to Adjudicate Unlawful Acts by Government Agencies and/or Officials (Onrechmatige Overheidsdaad) they are supposed to adjudicate actions against legal violations by government agencies and/or officials (onrechtmatige overheidsdaad). ) is fully competent to adjudicate at the State Administrative Court. However, regarding small claims for compensation at the State Administrative Court, members of the public can still submit claims for compensation through the District Court.